A LITERATURE REVIEW : PENGARUH PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DI SMA/MA : Project Based Learning, Berpikir Kreatif, Literatur Review, SMA/MA - izzah, mutia izzah (Al-Alam: Islamic Science Education Journal, 2025)
Creative thinking is one of the essential 21st-century skills that needs to be developed in the learning process in schools, especially at the high school level. Project-Based Learning (PjBL) is a learning model that is considered effective in fostering students' creative thinking skills through solving real-life problems in the form of projects. This study aims to systematically examine the effect of the PjBL model on students' creative thinking skills based on various previous research results. The method used is a literature study of relevant national and international scientific articles, supplemented by contextual data in the form of educational news in the mass media. Findings from the literature indicate that the implementation of PjBL can improve students' creative thinking skills, such as the ability to express original ideas, flexibility of thinking, elaboration, and fluency in conveying ideas. This literature study examines various recent studies (2020–2025) and examples of online news related to the implementation of PjBL. From these sources, it was found that PjBL consistently improves the ability of creative thinking aspects including fluency, flexibility, originality, and elaboration as well as improving student learning outcomes and motivation.